Removal of methyl violet 2B dye from aqueous solution using a magnetic composite as an adsorbent. (June 2015) - Bonetto, L.R.; Ferrarini, F.; de Marco, C.; Crespo, J.S.; Guégan, R.; Giovanela, M.
Abstract: Despite the important role of the textile industry in the global economy, its effluents generate deep concern with regard to treatment and disposal. Adsorption is a promising technique for the removal of textile color effluent at relatively low cost and with satisfactory efficiency. This study aimed to evaluate the adsorption capacity of a halloysite-magnetite-based composite in the removal of methyl violet 2B cationic dye. After preparation, the obtained composite was characterized by applying several instrumental techniques, including X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy and determination of pH at the point of zero charge. The influences of stirring rate, adsorbent mass, pH, initial concentration of dye and contact time on the adsorption process were also studied. The adsorption capacity of the composite was then investigated in a temperature-controlled batch system. The experimental results showed that the adsorption kinetics were better described using a pseudo-second-order model. Regarding the adsorption equilibrium, the experimental results suggest that both the Langmuir and Freundlich models were applicable. The thermodynamic data showed that dye adsorption onto the composite was spontaneous and endothermic and occurred by physisorption. The employed composite could also be regenerated at least four times using a 1.0 mol L −1 solution of NaOH as an eluent and was shown to be a promising adsorbent for the removal of cationic dyes.